1994
DOI: 10.2307/1542039
|View full text |Cite
|
Sign up to set email alerts
|

Ingestion of Ultraplankton by the Planktonic Larvae of the Crown-of-Thorns Starfish, Acanthaster planci

Abstract: There has been a debate over whether the growth and development of the larvae of the crown-of-thorns starfish Acanthaster planci are severely food-limited. This debate has raised a range of questions, including the one relating to the role of heterotrophic bacteria in the nutrition of larvae. In this study, the feeding rate of larvae on bacteria as well as on other ultraplankton (<5 {mu}m) was determined by counting the number of the fluorescence-labeled cells (FLC) in the gut after short incubation. Prelimina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 23 publications
6
28
0
Order By: Relevance
“…Okaji et al [68] demonstrated that clearance rates of larval feeding were significantly lower for smaller phytoplankton (1-2 µm) compared to phytoplankton with larger cell sizes (4-5 µm), even when smaller phytoplankton were overwhelmingly dominant. Also, heterotrophic bacteria appear to have a negligible role in larval nutrition [69]; though CoTS larvae are able to assimilate and utilize dissolved organic matter (DOM) in the water column [60,70], as well as coral-derived organic matter, such as mucus and associated microorganisms [28]. Mellin et al [26] tested for selective feeding by CoTS larvae among phytoplankton species of similar size (>5 µm).…”
Section: Question 2 (Larvae Andmentioning
confidence: 99%
“…Okaji et al [68] demonstrated that clearance rates of larval feeding were significantly lower for smaller phytoplankton (1-2 µm) compared to phytoplankton with larger cell sizes (4-5 µm), even when smaller phytoplankton were overwhelmingly dominant. Also, heterotrophic bacteria appear to have a negligible role in larval nutrition [69]; though CoTS larvae are able to assimilate and utilize dissolved organic matter (DOM) in the water column [60,70], as well as coral-derived organic matter, such as mucus and associated microorganisms [28]. Mellin et al [26] tested for selective feeding by CoTS larvae among phytoplankton species of similar size (>5 µm).…”
Section: Question 2 (Larvae Andmentioning
confidence: 99%
“…It has also been demonstrated that CoTS larvae can feed on other organic matter, such as mucus derived from corals [14]. As suggested by Ayukai [12], ingestion is likely controlled by other factors than algae size and concentration, with food quality potentially influencing CoTS feeding behaviour. While each of the aforementioned studies contributed knowledge to our understanding of the larval phase of this species, the corresponding experiments were short in duration (approximately 30 min) [12,13] or conducted using high food concentrations of little relevance to natural conditions [7].…”
Section: Introductionmentioning
confidence: 95%
“…Studies of larval feeding in CoTS conducted to date have focused on size selectivity and the influence of food concentration on feeding behaviour [7,12,13]. In particular, these investigations have demonstrated the ability of CoTS larvae to discriminate particle ingestion based on size (feeding in the range of 5-20 µm in diameter) and a modulatory effect of algal species on feeding and development.…”
Section: Introductionmentioning
confidence: 99%
“…However, laboratory experiments show that very low numbers of larvae are able to reach competency in food limited conditions [10,12,[22][23][24]. In addition, predation would also be a factor contributing to the mortality rate, with fish, such as damselfish, preying on CoTS larvae [25] in experimental aquarium conditions; however, the extent of predation in reef waters is not known.…”
Section: Mortality Of Cots At Different Life History Stagesmentioning
confidence: 99%